Design of Hierarchically Porous Carbons with Interlinked Hydrophilic and Hydrophobic Surface and Their Capacitive Behavior - Hao, Guang-Ping; Zhang, Qiang; Sin, Maria; Hippauf, Felix; Borchardt, Lars; Brunner, Eike; Kaskel, Stefan (Chemistry of Materials, 2016)
In this contribution, we report a general surface engineering strategy to transform nonpolar nanocarbons (e.g., carbon nanotube and graphene) into amphiphilic nanocarbons with unique ultrahydrophilic@ultrahydrophobic surface configuration and hierarchical structure by grafting a thin layer of metal-organic frameworks followed by pyrolysis and leaching. The outer ultrahydrophilic carbon layer features rich surface heterogeneity (B-/N-doping both up to ca. 10 at. %) and high density of microporosity, while the inner nonpolar CNT or graphene provides a high electronic conductivity. The unique bipolar surface and high heterogeneity as well as highly accessible hierarchical structures render this family of nanocarbons capable of a high surface efficiency under both aqueous and organic conditions, as it is reflected in the behavior of the electrodes for supercapacitors by comparing a wide range of highly porous nonpolar carbons. The bipolar hierarchical carbons' efficiency in terms of areal capacitance and energy density are 3-6 times and 2-3 times higher than that of typical benchmark materials (e.g., commercially popular YP-50F carbons, CNT, and graphene etc.). More importantly, the study of this series of model carbon materials may help researchers to understand in-depth how carbon surface chemistry with a high density of doping sites influences the wetting, transport, and electrosorption behavior of charged ions in aqueous and organic conditions.
CRIS-Team Scopus Importer:2023-03-20